Knowledge about causes and prevention of oral diseases among higher secondary school students in Vellore District, Tamil Nadu, India: A cross-sectional survey - Delfin Lovelina Francis; Kumara Raja Balasubramanian; R Durga; Chitraa R Chandran (Wolters Kluwer Medknow Publications, 2018)
Background: Awareness regarding oral diseases and its prevention aids in the development of correct oral health practices, thereby controlling oro-dental problems; hence, this study aimed to evaluate the level of oral health knowledge pertaining to its causes and prevention among higher secondary school students in Walajapet, Vellore district, India. Materials and Methods: The survey was carried out among 400 schoolchildren who were in the age group of 16-18 years studying in various schools of Walajapet in Vellore district. Data on knowledge about oral diseases were collected by means of self-administered questionnaire. The results were analyzed by descriptive statistics and Chi-square test using Statistical Package for the Social Sciences version 19. P < 0.05 was considered statistically significant. Results: A total of 400 secondary school students with an age range of 16-18 years and mean age of 17.2 ± 10.44 years participated in the study. About 324 (81.0%) secondary school students had adequate level of knowledge on causes and prevention dental caries, 267 (66.7%) school students were aware of causes and prevention of periodontal diseases, only 195 (48.7%) school students had awareness on cause and prevention of oral cancer, and 305 (76.2%) students were familiar with causes and prevention of dental malocclusion. Conclusion: Majority of schoolchildren showed adequate knowledge toward causes and prevention of dental caries, periodontal disease, and dental malocclusion but had inadequate knowledge toward oral cancer.